Sexuality, fertility and family planning characteristics of married women aged 15 to 19 years in Ethiopia, Nigeria and Tanzania: a comparative analysis of cross-sectional data - Christina J. Atchison; Jenny A. Cresswell; Saidi Kapiga; Mussa Kelvin Nsanya; Emily E. Crawford; Mohammed Mussa; Christian Bottomley; James R. Hargreaves; Aoife M. Doyle (Reproductive Health, 2019)
Abstract Background Adolescents 360 (A360) is an initiative being rolled out across Ethiopia, Nigeria and Tanzania with the aim of increasing uptake of voluntary modern contraception among sexually active women aged 15 to 19 years. Using evaluation baseline survey data, we described key sexuality, fertility and contraceptive use characteristics of married women aged 15 to 19 years living in three sub-national settings. Methods Cross-sectional baseline surveys of married women aged 15 to 19 years were conducted in Oromia (Ethiopia), Nasarawa (Northern Nigeria), and Mwanza (Tanzania) between August 2017 and February 2018. We also interviewed the husbands of a sub-group of married respondents to measure spousal acceptance and support for adolescent women to use modern contraception. A clustered sampling design was used in all three countries. We produced descriptive statistics on the socio-demographic and sexual and reproductive health characteristics of married women aged 15 to 19 years by study setting. Results In Oromia, Nasarawa and Mwanza, 31.4% (327/1198), 27.4% (1321/4816) and 7.5% (15/201) of married women surveyed had no education, and 68.3, 81.3 and 83.1% had ever been pregnant, respectively. Unmet need for modern contraception was 20.5, 21.9 and 32.0% in married women in Oromia, Nasarawa and Mwanza, made up almost entirely of unmet need for spacing. The vast majority of married women surveyed in Oromia (89.1%) and Mwanza (90.1%) had seen or heard about contraception in the last 12 months, compared to 30.1% of those surveyed in Nasarawa. Modern contraceptive prevalence (mCPR) was highest in married women aged 15 to 19 years in Oromia (47.2%), followed by Mwanza (19.4%) and Nasarawa (8.7%). Of those using a modern method of contraception in Oromia, 93.4% were using injectables or long-acting methods, compared to 49.4% in Nasarawa and 69.6% in Mwanza. Conclusions Overall, unmet need for modern contraception is high among married women aged 15 to 19 years across the three settings. mCPR for married women aged 15 to 19 years is low in Nasarawa and Mwanza. Ultimately, no single intervention will suit all situations, but improving the quality, analyses and utilisation of subnational data can help decision-makers design more context specific interventions.